Structures, strain analyses, and 40Ar/39Ar ages of blueschist‐bearing Heilongjiang Complex (NE China): Implications for the Mesozoic tectonic evolution of NE China. (22nd October 2018) - Aouizerat, Arthur; Xiao, Wenjiao; Schulmann, Karel; Jeřábek, Petr; Monié, Patrick; Zhou, Jian‐Bo; Zhang, Jinjiang; Ao, Songjian; Li, Rui; Li, Yongchen; Esmaeili, Rasoul
Abstract : The high‐pressure Heilongjiang Complex belongs to a Jurassic accretionary complex in Yilan area, NE China. The complex is located in the junction of three orogenic systems in the NE Asia: the E‐W‐striking Central Asian Orogenic Belt (CAOB), the N‐S‐striking Paleo‐Pacific system, and the ENE‐WSW‐striking Mongol‐Okhotsk system. Thus, a detailed tectono‐metamorphic analysis coupled with accurate radiometric dating of the Heilongjiang Complex provided in this study represent important evidence for understanding the complex interactions between the three orogenic systems in the Late‐Palaeozoic to Mesozoic. New structural and microstructural data combined with the strain analysis highlight the presence of three distinct deformation events affecting the high‐pressure Heilongjiang Complex. The first deformation event D1 is related to development of blueschist facies prolate to plane strain fabrics that were subsequently reworked by the blueschist‐amphibolite facies event D2 that transposed all previous structures by the main west‐dipping schistosity. This planar fabric was folded by upright F3 folds and heterogeneously reworked by greenschist facies E‐W‐striking vertical cleavage during large scale N‐S shortening. Each deformation event was related to specific strain fabrics and metamorphic conditions highlighting dynamic evolution of the subduction complex during burial, exhumation, and final shortening. The first D1 event is related to westward directed prograde constrictional flow and progressive dismembering of competent mafic, ultramafic layers, and quartzites in highly stretched meta‐sedimentary matrix. This mélange was folded by recumbent detachment folds resulting in emplacement of the exhumed unit progressively reaching amphibolite facies conditions atop of W‐WSW‐dipping channel. This event is associated with dominant flattening implying increasing mechanical coupling between the colliding Songliao and Jiamusi blocks. Subsequently, the accreted subduction complex was reworked during N‐S‐directed horizontal shortening. This event was associated with an important post‐buckle flattening of fold limbs and rotation of competent blocks with inherited D1 and D2 strain ellipsoids along F3 fold axes. Our new 40 Ar‐ 39 Ar plateau ages on muscovite and phengite (173–177 Ma), together with previous radiometric data, are interpreted as reflecting exhumation of subduction channel during the blueschist‐amphibolite facies event while the N‐S shortening (D3) probably operated in Late Jurassic as indicated by some previously published cooling ages ( 140–160 Ma). The westward‐oriented subduction and exhumation fabrics of the high‐pressure Heilongjiang accretionary complex followed by N‐S‐directed upright folding are interpreted to reflect transition from E‐W Pacific subduction regime to N‐S‐directed shortening related to the closure of the Mongol‐Okhotsk Ocean.